Achievements of the EORTC Soft Tissue and Bone Sarcoma Group - Hohenberger, Peter (European journal of cancer. EJC Supplements, 2012)
The EORTC Soft Tissue and Bone Sarcoma Group (STBSG) develops, stimulates, and coordinates studies on all aspects of sarcomas, and over the years they have made significant achievements in the research and treatment of sarcomas. Through EORTC trials 62001, 62005, 62024, and 62063, they established imatinib in the treatment of gastrointestinal stromal tumors (GIST). Because the STBSG has conducted a large number of clinical trials in advanced disease and collected and stored all trial data in a consistent format, they were able to use these data in retrospective studies and develop progression-free survival as the primary endpoint for phase II studies in advanced soft-tissue sarcoma. This database also served as a basis for research projects analyzing subgroups of tumors like malignant peripheral nerve sheath tumors, and for exploring prognostic and predictive factors for first-line chemotherapy including ifosfamide, and proved to be of value when analyzing the results of adjuvant chemotherapy in adolescents and young adults as compared to the adult patient population. This article describes these achievements and looks into the future strategy of the STBSG.